Maternal Immunization Knowledge, Attitudes, and Practices on Tetanus Toxoid Vaccination Among Pregnant Teenagers - Alvarez, Ma. Chaela; Lumaguey, Marshall Jeanne; Mimay, Pauline Erika; Cruz, Alyana; Quintana, Marc Lester; Lajara, Vivian (Journal of Interdisciplinary Perspectives, 2026)
Tetanus toxoid vaccination is a key maternal immunization intervention for preventing maternal and neonatal tetanus, a highly fatal yet preventable condition. Despite free provision by the Philippine Department of Health, vaccination uptake among pregnant teenagers remains inconsistent. However, there is limited local evidence examining the knowledge, attitudes, and practices related to tetanus toxoid vaccination among pregnant adolescents, particularly in community-based settings. This study assessed levels of knowledge, attitudes, and practices regarding tetanus toxoid vaccination among pregnant teenagers in San Pablo City, Laguna, and examined differences by selected socio-demographic characteristics. A descriptive-comparative quantitative design was utilized, involving 65 pregnant teenagers selected through purposive sampling from barangays with high teenage pregnancy prevalence. Data were collected using a validated and reliability-tested questionnaire. Statistical analyses included frequency and percentage, mean and standard deviation, and the Mann–Whitney U test and Kruskal–Wallis test. Findings indicated moderate knowledge, positive attitudes, and generally adequate but inconsistent vaccination practices. Significant differences in knowledge were observed across age and educational attainment groups, whereas attitudes differed significantly by civil status. No significant differences were found in practices across socio-demographic variables. These findings emphasize the need for adolescent-centered maternal immunization education, early engagement in antenatal care, and supportive vaccination counseling. As a practical output, a Personalized Tetanus Toxoid Immunization Journal was developed to enhance dose monitoring, awareness, and vaccination compliance among pregnant teenagers. Strengthening youth focused maternal immunization initiatives may help reduce the risk of maternal and neonatal tetanus at the community level.